BUSINESS SUCCESS FACTORS IN IRANIAN SMALL AND MEDIUM ENTERPRISES SECTOR (SMES) (Singaporean Journal of Business Economics and Management, 2018)
Introduction The importance of Small and Medium Enterprises sector is well recognized from its significant contribution to the socio-economic objectives of the country like generation of employment, output, exports and fostering entrepreneurship. Case description One of the requirements for growth, creativity as well as entrepreneurship within societies is to study their success process. Our sample includes 230 Small and Medium Enterprises that were established during 2004 to 2016 in Fars province. Data was collected through questioners around general "manager/entrepreneur" among all categories of small and medium business. Discussion and Evaluation The purpose of this study is to investigate factors which effect on success entrepreneurs in Small and Medium Enterprises sector. The results of this study are helpful to the policy makers to frame suitable entrepreneurship development strategies to develop entrepreneurs. Conclusions Our findings revealed significant difference between the internal and external factors for success of the business. The study revealed that there is a significant difference between internal and external factors on the success of the business. It is concluded that there is high effect of success of units by strong believing of internal factors of the business.Keywords: Entrepreneurship-Success factors-SMEs-IranAbstractIntroduction The importance of Small and Medium Enterprises sector is well recognized from its significant contribution to the socio-economic objectives of the country like generation of employment, output, exports and fostering entrepreneurship. Case description One of the requirements for growth, creativity as well as entrepreneurship within societies is to study their success process. Our sample includes 230 Small and Medium Enterprises that were established during 2004 to 2016 in Fars province. Data was collected through questioners around general "manager/entrepreneur" among all categories of small and medium business. Discussion and Evaluation The purpose of this study is to investigate factors which effect on success entrepreneurs in Small and Medium Enterprises sector. The results of this study are helpful to the policy makers to frame suitable entrepreneurship development strategies to develop entrepreneurs. Conclusions Our findings revealed significant difference between the internal and external factors for success of the business. The study revealed that there is a significant difference between internal and external factors on the success of the business. It is concluded that there is high effect of success of units by strong believing of internal factors of the business.